Cronology and environmental impact of land use on Ceveiro Microbasin in Piracicaba region, Brazil - Fiorio, Peterson Ricardo; Demattê, José Alexandre Melo; Sparovek, Gerd (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this work was to evaluate the chronology and environmental impact of the land use on Ceveiro Microbasin, in Piracicaba, São Paulo State, during the years of 1962, 1965, 1978 and 1995. Photointerpretation and geoprocessing were used, allowing a fast and efficient integration of the data. The soils of the area are basically Entisols and Ultisols. Annual crops that in 1965 occupied 42% of the Microbasin area, in 1995 occupied 0,15%. In that same period, sugarcane passed from 16% to 66%, causing the decrease of the annual crops. The largest growth of sugarcane crop occurred from 1978 to 1995, characterizing the influence of the government incentives for its cultivation. Pastures and reforestations also contributed to the expansion of sugarcane, with a decrease in area of 48% for pastures and 42% for reforestation. Native forest and urban areas presented an increase from 1962 to 1995. The environmental impact in the Ceveiro Microbasin is indicated by Vila de Artemis dam, that from 1978 to 1995 decreased its area in 50% due to silting.